Marketing Strategy and Economic Analysis in Increasing Company Profitability - Ihdina Gustina (Outline Publisher, 2026)
Purpose: This study aims to analyze the influence of brand image, distribution channels, market demand, and government policies on company profitability, focusing on how marketing-related factors and external policy environments contribute to financial performance in Indonesian manufacturing companies. Methods: A quantitative research approach using multiple linear regression analysis was employed. Data were collected from 80 respondents, including marketing and finance managers in manufacturing companies across Indonesia. The data were analyzed using SPSS with partial (t-test) and simultaneous (F-test) significance tests. Results: The regression analysis results show that brand image, distribution channels, market demand, and government policies each have a positive and significant effect on company profitability. Simultaneously, these four variables also jointly significantly impact profitability, indicating that a combination of internal marketing strengths and supportive external policies leads to better financial outcomes. Conclusions: This study concludes that brand image, distribution channels, market demand, and government policies are crucial for increasing corporate profitability. Internal marketing factors and external policies should be managed synergistically to achieve sustainable growth. Companies are encouraged to strengthen brand equity, optimize distribution networks, and enhance competitiveness. Originality/Value: This research contributes to the literature by integrating marketing and policy perspectives to explain company profitability within Indonesia’s manufacturing sector. It highlights the combined effect of brand strategy, distribution, market dynamics, and government policy, offering valuable insights for managers and policymakers.